Effects of raised temperature of sulfate solutions on the sulfate resistance of mortars with and without silica fume - Aköz, F; Türker, F; Koral, S; Yüzer, N (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Effect of raised temperature of sodium sulfate and magnesium sulfate solutions on the resistance of mortars was investigated. Experimental study was carried out on mortars with and without silica fume. Sulfate concentration was 18000 mg/L as SO42- for the sodium sulfate and 13000 mg/L magnesium sulfate solutions. Temperatures of solutions were 20 and 40 degrees C. Some physical and mechanical properties were tested during the 300 days of sulfate exposure. Test results showed that raised solution temperature did not accelerate the deterioration of mortars under the conditions used in this research. Moreover, raised temperature improved many properties of the specimens. It can be suggested that there are some problems with raising the temperature of sulfate solution as an accelerated test method. (C) 1999 Elsevier Science Ltd, All rights reserved.
Keywords: acceleration; durability; silica fume; sulfate attack; temperature; PORTLAND-CEMENT PASTE; MAGNESIUM-SULFATE; ATTACK; CONCRETE; Construction & Building Technology; Materials Science